Reference values for oxygen saturation from sea level to the highest human habitation in the Andes in acclimatised persons. Issue 8 (20th October 2017) - Rojas-Camayo, Jose; Mejia, Christian Richard; Callacondo, David; Dawson, Jennifer A; Posso, Margarita; Galvan, Cesar Alberto; Davila-Arango, Nadia; Bravo, Erick Anibal; Loescher, Viky Yanina; Padilla-Deza, Magaly Milagros; Rojas-Valero, Nora; Velasquez-Chavez, Gary; et al.
Abstract : Oxygen saturation, measured by pulse oximetry (SpO2 ), is a vital clinical measure. Our descriptive, cross-sectional study describes SpO2 measurements from 6289 healthy subjects from age 1 to 80 years at 15 locations from sea level up to the highest permanent human habitation. Oxygen saturation measurements are illustrated as percentiles. As altitude increased, SpO2 decreased, especially at altitudes above 2500 m. The increase in altitude had a significant impact on SpO2 measurements for all age groups. Our data provide a reference range for expected SpO2 measurements in people from 1 to 80 years from sea level to the highest city in the world.